Thermal expansion behaviour of orthopyroxenes: the role of the Fe-Mn substitution. (2nd January 2018) - Scandolo, L.; Mazzucchelli, M. L.; Alvaro, M.; Nestola, F.; Pandolfo, F.; Domeneghetti, M. C.
Abstract: Two Pbca orthopyroxene samples, donpeacorite (DP N.1) and enstatite (B22 N.60) with chemical formulae Mn0.54 Ca0.03 Mg1.43 Si2 O6 (XMn = 0.27) and Fe0.54Ca0.03 Mg1.4 3Si2 O6 (XFe = 0.27), respectively, were investigated by single-crystal X-ray diffraction at high-temperature conditions. The nearly identical XFe and XMn make the two samples the perfect candidates to investigate the effect of the compositional change at the M 2 site (i.e. Fe-Mn substitution) on the thermal expansion behaviour of orthopyroxenes. Therefore, the unit-cell parameter thermal expansion behaviour of both samples has been investigated in the temperature range between room T and 1073 K. No evidence for phase transitions was found over that range. The two samples have been previously disordered with an ex situ annealing at ∼1273 K. The unit-cell parameters and volume thermal expansion data, collected on the disordered samples, have been fitted to a Fei Equation of State (EoS) and the following coefficients obtained: V0 = 853.35(4) Å 3, αV, 303K = 2.31(24) × 10 –5 K –1 and V0 = 845.40(6) Å 3, αV, 303K = 2.51(25) × 10 –5 K –1 for DP N.1 and B22 N.60, respectively. While there is no difference in the volume thermal expansion coefficient as a function of composition and the expansion along theb direction is nearly identical for both samples, slight differences have been found alonga andc lattice directions. The thermal expansion along thea direction is counterbalanced by that alongc being responsible for the changes in lattice expansion scheme from αb > αc > αa at room T, to αc > αb > αa at high T. Therefore, as a result of the different behaviour alonga andc, the unit-cell volume thermal expansion for both samples is identical within estimated standard deviations. The negligible effect of the Fe-Mn substitution on the bulk thermal expansion can be applied when dealing with geothermobarometry based on the elastic host-inclusion approach (e.g. Nestola et al., 2011; Howell et al., 2010; Angel et al., 2014 a, b, 2015). In fact, though the compressibility effect is still not known, the nearly identical thermal expansion coefficients will not affect the entrapment pressure ( P e ).